Concentration-dependent photostability of phycocyanin under UV-A and UV-B irradiation - Nurfarida Ulfah; Helis Siti Halimatul Munawaroh; Gun Gun Gumilar (Acta Biochimica Indonesiana, 2025)
Background: Indonesia's tropical location results in intense UV exposure, necessitating effective photoprotective agents. Phycocyanin from Spirulina platensis shows promise as a natural sunscreen ingredient, yet systematic evaluation of its photostability across concentrations remains limited. Objectives: To evaluate phycocyanin stability and antioxidant activity under UV-A and UV-B irradiation across different concentrations. Methods: Phycocyanin (200, 250, 300, and 350 ppm) was exposed to UV-A (365 nm, 2.8 mW/cm²) and UV-B (312 nm, 3.2 mW/cm²) irradiation for up to 30 minutes. Pigment concentration and DPPH radical scavenging activity were measured using UV-Vis spectrophotometry. Results: Phycocyanin exhibited concentration-dependent stability, with 300–350 ppm demonstrating optimal performance. UV-B caused greater degradation than UV-A, with concentration losses of 14.19–43.43 ppm (UV-B) versus 6.85–16.63 ppm (UV-A) after 30 minutes. Antioxidant activity decreased minimally under UV-A (≤1.85%) but more substantially under UV-B (≤1.97%). The 350 ppm concentration showed highest stability and antioxidant retention (98.9% and 98.0%, respectively). Conclusion: The 300–350 ppm range represents the optimal concentration for photoprotective applications, supporting phycocyanin's potential as a natural sunscreen ingredient.